THERMAL ASSYMETRY OF THE ORAL MUCOSA RELATED TO INFECTIOUS AND PROSTHETIC FACTORS: A THERMOGRAPHIC STUDY - Laura Iosif; Marina Imre; Andreea Cristiana Didilescu; Ana Maria Cristina Ţâncu; Oana Elena Amza; Georgiana Florentina Gheorghe; Ruxandra Ionela Sfeatcu; Radu Ilinca; Bogdan Alexandru Dimitriu (Romanian Journal of Oral Rehabilitation)
Aim of the study. Infrared thermography can be successfully used to obtain data about the functionality of the denture bearing mucosa of removable denture wearers. The purpose of the study was to test the distribution of the thermal field as concerns the symmetry and uniformity at the level of the support maxillary mucosa of mobile prosthesis wearers, with or without Candida-associated denture stomatitis (CADS). Materials and Methods. A cross-sectional study was conducted upon subjects with different prosthetic status (n=66) placed into five groups: G1- complete denture wearers on the maxillary arch with CADS (n=22); G2- complete denture wearers on the maxillary arch with recent prostheses (n=12); G3- complete denture wearers on the maxillary arch with old prostheses (n=12); G4 – edentulous subjects without maxillary dentures (n=10); G5- dentate subjects (n=10). Biological samples for Candida were taken from all subjects, with inoculations on Sabouraud Dextrose medium enriched with chloramphenicol and thermography with ThermaCAM PM350 at the level of the maxillary mucosa and of the inner sides of the upper dentures for the subjects distributed in G1-G3. Results. The proportion of subjects for which the distribution of the thermal field at the level of the mucosa showed neither symmetry nor uniformity was significantly higher for the cases with CADS compared to the other 4 groups (symmetry/uniformity: p < 0.0001); the share of subjects for which the distribution of the thermal field showed neither symmetry nor uniformity was statistically significantly higher among the edentulous with CADS, compared to the other 2 groups (symmetry p < 0.0001; uniformity p = 0.004). Although the statistical threshold was not reached, among all the clinical cases with intact maxillary mucosa, the most frequent disturbances of the thermal architecture were found among the wearers of long-standing maxillary prostheses. Conclusion. Asymmetrical temperature distribution on the maxillary denture bearing mucosa as detected from thermal images coincides well with infective-inflammatory conditions such as Candida-associated denture stomatitis but can also be frequently detected in healthy maxillary mucosa in wearers of old complete dentures.